Organizational citizenship behavior: The psychometric properties of the questionnaire - Bagdžiūnienė, D.; Lazauskaitė-Zabielskė, J.; Urbanavičiūtė, I. (Psichologija, 2013)
Organizational citizenship behaviour (OCB) is defined as “individual behaviour that is discretionary and not directly or explicitly recognized by the formal reward system and in the aggregate promotes the efficient and effective functioning of the organization” (Organ et al., 2006). The concept of OCB was initially introduced in the 1980s, and it soon became a widely internationally and cross-culturally investigated phenomenon. Empirical evidence suggests that OCB is related to a number of positive outcomes at individual, group, and organizational levels. Therefore, the last three decades were abundant in studies aimed towards the clarification of OCB dimensionality and identifying its antecedents and consequences in a variety of settings. The Lithuanian research on this topic, however, is scarce. Due to the fact that the construct of OCB is quite culturally sensitive and studies on OCB in Lithuania are still in their preliminary phase, there is no valid and reliable instrument that could be used to measure it. Therefore, the main goal of the present study was to gather data on OCB in a Lithuanian employee sample and to develop an instrument that would enable measuring citizenship behaviours in Lithuanian organizations. In order to develop the Lithuanian version of the OCB questionnaire, we chose an integrated approach, i.e. first an extensive theoretical analysis of classical OCB models had been carried out. Next, three qualified psychologists selected the OCB dimensions that appeared most commonly across different OCB models. Finally, based on this selection, a composite 53-item questionnaire was developed, encompassing various aspects of organizational citizenship. The study was carried out in a sample of 289 employees from a number of Lithuanian organizations (22.1% of male, 77.9% of females; mean age 32.32 years). To identify the dimensionality of OCB, exploratory factor analysis was conducted. Next, after conducting the item analysis, 29 items were retained and repeatedly factor-analyzed. The results have revealed five OCB dimensions: altruism, courtesy, civic virtue, conscientiousness, and initiative. An overall questionnaire and all its subscales have proven to have high reliability coefficients (Cronbach alphas > 0.76). Moreover, the analysis has shown that the distinguished OCB dimensions were separable from in-role performance and correlated to a number of factors reported as the most common OCB correlates (e.g., organizational identity, commitment, and job satisfaction). To generalize, preliminary findings strongly suggest that the Lithuanian version of the OCB questionnaire, developed in this study, has adequate psychometric properties and is congruent to the classical concept of OCB. Naturally, in the future, additional empirical evidence will be necessary to support the identified OCB factor structure.